Genealogi Masyarakat Madura Dan Jawa: Studi Budaya Pedhalungan Di Kabupaten Jember - Prayogi, Bagus (Habitus : Jurnal Pendidikan, Sosiologi, dan Antropologi, 2022)
Jember dikenal sebagai kota pendalungan, meskipun demikian pendalungan sebagai identitas baru saja digunakan beberapa tahun terakhir. Hal ini pula yang menimbulkan kontestasi antar masyarakat Jember ada yang menerima dan ada yang menolak. keikutsertaan bupati saat itu sebagai kampanye tahunan membuat gaduh dan syarat akan kepentingan pragmatis di dalamya. Masyarakat jember sendiri terdiri atas masyarakat Madura dan Jawa. pendalungan muncul akibat akulturasi antara masyarakat Madura dan Jawa. Sekat-sekat Jawa-Madura masih tampak sangat jelas, dan pendalungan sebgai suatu identitas Jember diidikasikan memiliki kepentingan yang sistematis dari para birokrat. Maka dari itu Fokus dari penelitian pada Genealogi dari masyarakat madura dan jawa terhadap budaya pendhalungan. Maka dari itu ada tiga rumusan masalah dalam penelitian ini pertama, bagaimana adat madura dan Jawa secara komprehensif? Kedua, bagaimana genealogi antara masyarakat Madura dan Jawa yang berada di Jember? Ketiga, Bagaimana pendhalungan tumbuh di sekitaran masyarakat Madura dan Jawa? Penelitian ini menggunakan metode kualitatif deskriptif. Adapaun teknik pengumpulan data dengan observasi, kuisioner, wawancara, serta dokumentasi, sedangkan pendekatan yang dilakukan adalah pendekatan etnografi. Untuk itu tujuan dari paper ini yaitu: pertama, mengetahui budaya Masyarakat Madura dan Jawa yang berada di Jember secara komrehesif. Kedua, mengetahui kontestasi antara Masyarakat Madura dan Jawa. Ketiga, mengetahui budaya pendhalungan terhadap masyarakat Madura dan Jawa Kata Kunci: Genealogi; Madura dan Jawa; Pendhalungan  Abstract Jember is known as the city of pendalungan, although pendalungan as an identity has only been used in the last few years. This also causes contestation among the people of Jember, some who accept and some who reject. The regent's participation at that time as an annual campaign made noise and conditions for pragmatic interests in it. Jember community itself consists of the Madurese and Javanese. Pendalungan emerged as a result of acculturation between the Madurese and Javanese people. The boundaries of Java-Madura are still apparent, and pendalungan as a Jember identity is indicated to have a systematic interest from the bureaucrats. Therefore, the focus of research on the genealogy of the Madurese and Javanese people towards the pendhalungan culture. Therefore, there are three formulations of the problem in this study; first, How is the Madura and Javanese customs comprehensively? Second, how is the genealogy between the Madurese and Javanese people in Jember? Third, how does pendhalungan grow around the Madurese and Javanese communities? This research uses the descriptive qualitative method for the data collection techniques by observation, questionnaires, interviews, and documentation. For this reason, the objectives of this paper are: first, to know the culture of the Madurese and Javanese people in Jember comprehensively. Second, knowing the contestation between the Madurese and Javanese people. Third, understanding the pendhalungan culture for the Madurese and Javanese people. How does pendhalungan grow around the Madurese and Javanese people? This research uses the descriptive qualitative method for the data collection techniques by observation, questionnaires, interviews, and documentation. For this reason, the objectives of this paper are: first, to know the culture of the Madurese and Javanese people in Jember comprehensively. Second, knowing the contestation between the Madurese and Javanese people. Third, understanding the pendhalungan culture of the Madurese and Javanese people. How does pendhalungan grow around the Madurese and Javanese people? This research uses the descriptive qualitative method for the data collection techniques by observation, questionnaires, interviews, and documentation. For this reason, the objectives of this paper are: first, to know the culture of the Madurese and Javanese people in Jember comprehensively. Second, knowing the contestation between the Madurese and Javanese people. Third, learning the pendhalungan culture of the Madurese and Javanese people and understanding the culture of the Madurese and Javanese people in Jember comprehensively. Second, knowing the contestation between the Madurese and Javanese people. Third, learning the pendhalungan culture of the Madurese and Javanese people, first, understanding the culture of the Madurese and Javanese people in Jember comprehensively. Second, knowing the contestation between the Madurese and Javanese people. Third, learning the pendhalungan culture of the Madurese and Javanese people. Keywords: Genealogy; Madura and Java; Pendhalungan